Mesenchymal Chondrosarcoma: A Rare Aggressive Variant of Chondrosarcoma - Jhunjhunwala, Adarsh Kumar; Ghosh, Arnab; Shrestha, Manish Kiran; Ghartimagar, Dilasma; Thapa, Sushma; Regmi, Sudeep; Dhakal, Binod (Nepalese Medical Journal, 2020)
A 15-year-old boy reported a 2-month history of severe left thigh pain Physical examination revealed left thigh swelling measuring 6x5 cm. X-ray of the region showed mixed lytic and sclerotic lesion involving the femoral head and neck. A Computed Tomography scan showed mixed lytic and sclerotic lesion involving the femoral head and neck with cortical irregularity and mild periosteal reaction with associated soft tissue in the anterior aspect. Magnetic resonance imaging demonstrated heterogeneous signal intensity lesion with areas of sclerosis involving the femoral head and neck. The large associated soft tissue in the anterior aspect appears predominantly hyperintense on T2W images. On post-contrast axial and sagittal images, heterogeneous enhancement with areas of necrosis involving soft tissue was seen. A presumptive radiological differential diagnosis of Ewing Sarcoma and Osteosarcoma was made. However, on histopathology, it was a case of mesenchymal chondrosarcoma.